Communicative activities for EAP - Guse, Jenni, 1950- (Cambridge handbooks for language teachers, 2011)
"Do you need to supplement an EAP course with fun, interactive activities that address the serious aspirations of academically-focussed students? Communicative Activities for EAP provides innovative EAP teaching ideas suitable for a wide range of contexts. This is an invaluable handbook for new, experienced or relief teachers of language support programmes, as well as for those teaching intensive language courses for undergraduate and postgraduate students in EFL and ESL/EAL contexts. The key principles of communication in the classroom, authenticity in terms of tasks and texts, learner autonomy, and critical thinking and analysis underpin all the activities, and typical academic topics are used as examples in every case. For ease of access, the activities are organised into six chapters: Speaking, Listening, Reading, Writing, Vocabulary development and Grammar. The accompanying CD-ROM contains a bank of print-ready photocopiable material"-- Anotace od vydavatele